PENERAPAN ASAS PERSAMAAN HAK DALAM PENGUASAAN DAN PENGGUNAAN TANAH MENURUT UNDANG-UNDANG NOMOR 5 TAHUN 1960 TENTANG PERATURAN DASAR POKOK-POKOK AGRARIA DI DAERAH ISTIMEWA YOGYAKARTA (STUDI KASUS PUTUSAN PENGADILAN NEGERI YOGYAKARTA NOMOR 132/PDT.G/2017/PN.YYK.) - Defki Gunawan; Hasni Hasni (Jurnal Hukum Adigama, 2020)
Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles (UUPA) has already been enacted in Indonesia, but in the Special Region of Yogyakarta (DIY) it is in conflict with the Deputy Head of DIY Regional Instruction Number K.898/I/A/1975 regarding prohibition of ownership and control of land rights for Non-Indigenous Indonesians in Yogyakarta. Problems encountered in writing this thesis are how the application of the principle of equal rights in the control and use of land in the Special Region of Yogyakarta and how judges consider it in the Decision of the Yogyakarta District Court Number 132/Pdt.G/2017/PN.Yyk, is it in accordance with the principle of legal subjects in the LoGA. The research method used in writing this thesis is normative legal research. The results showed that the provisions on granting land rights to a Non-Indigenous Indonesian citizen in DIY based on the Instruction of Deputy Regional Head of DIY Number K.898/I/A/1975 were due to 2 reasons namely historical reasons and secondly because of fear of land being controlled by non-indigenous Indonesian citizens and the issuance of Instruction Deputy Regional Head of DIY is not without reasoning and thought. According to the author, the publication of this circular letter was a decision taken by Sri Sultan Hamengkubowono X as a leader as well as a King who protected the region and its people.